"Every child that is a foster child is marked from the beginning": The home-school communication experiences of foster parents of children with disabilities. (January 2018) - Mires, Carolyn B.; Lee, David L.; McNaughton, David
Abstract: This study investigated the perceptions of foster parents of children with disabilities concerning their interactions with school personnel. We conducted semi-structured interviews with 7 foster parents of 6 children with disabilities (age range = 5–16). A qualitative analysis of the interviews resulted in the identification of five thematic areas, including foster parent perceptions of: (a) the role of the foster parent, (b) the efficacy of the foster parent in helping the child learn, (c) invitations to involvement from the school (d) invitations to involvement from the child, and (e) foster child experiences in the school system. Marked differences were found in the perceptions of the perceptions in foster parents of elementary and secondary age students. It is clear that foster parents who take on an active role in their child's education experienced positive relationships with their child's school. Foster parents who take a passive role in their partnerships with the schools experienced increased difficulty maintaining motivation to continue in their efforts to increase collaboration and involvement with the schools. They indicated a sense of anger, distrust, and even hostility towards the schools. Based on the findings, recommendations are provided for improving home-school relationships, and addressing obstacles to successful school partnerships with foster families.